2015
DOI: 10.1002/jcc.24214
|View full text |Cite
|
Sign up to set email alerts
|

Glucose transformation to 5‐hydroxymethylfurfural in acidic ionic liquid: A quantum mechanical study

Abstract: Isomerization and transformation of glucose and fructose to 5-hydroxymethylfurfural (HMF) in both ionic liquids (ILs) and water has been studied by the reference interaction site model self-consistent field spatial electron density distribution (RISM-SCF-SEDD) method coupled with ab initio electronic structure theory, namely coupled cluster single, double, and perturbative triple excitation (CCSD(T)). Glucose isomerization to fructose has been investigated via cyclic and open chain mechanisms. In water, the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 86 publications
0
12
0
Order By: Relevance
“…The majority of papers reporting the conversion of carbohydrates in alternative solvents focus on the production of HMF. A theoretical comparative study of reaction mechanisms in water and the IL 1,3‐dimethylimidazolium chloride ([C 1 mim]Cl) found that major differences in outcomes were due to solvent effects in water and IL media . First, it should be noted that deprotonation of the C2 hydroxyl group may be performed by the Cl − ion of [C 1 mim]Cl, similar to the C2–C1 hydride shift proposed during glucose–fructose isomerization catalyzed by Lewis acids in water (Scheme ).…”
Section: Transformation Of Saccharides In Ionic Liquidsmentioning
confidence: 99%
“…The majority of papers reporting the conversion of carbohydrates in alternative solvents focus on the production of HMF. A theoretical comparative study of reaction mechanisms in water and the IL 1,3‐dimethylimidazolium chloride ([C 1 mim]Cl) found that major differences in outcomes were due to solvent effects in water and IL media . First, it should be noted that deprotonation of the C2 hydroxyl group may be performed by the Cl − ion of [C 1 mim]Cl, similar to the C2–C1 hydride shift proposed during glucose–fructose isomerization catalyzed by Lewis acids in water (Scheme ).…”
Section: Transformation Of Saccharides In Ionic Liquidsmentioning
confidence: 99%
“…In addition, multiscale modeling as a tool for understanding biomass processing has been discussed . Glucose transformation to HMF in water was also studied by Car–Parrinello molecular dynamics , and by the reference interaction site model and coupled clusters ab initio calculations . Furthermore, Miyamoto et al carried out molecular dynamics simulation of dissociation behavior of cellulose treated with hot-compressed water.…”
Section: Introductionmentioning
confidence: 99%
“…In the reaction medium used in this study, the carbonic acid formed from the reaction of water with the dissolved carbon dioxide provides the Bronsted acid that promotes the formation of HMF. The mechanism of the dehydration of fructose to form HMF, particularly in an acidic environment, has already been reported in a number of studies. Therefore, this work focused on specific points in the reaction pathway where isopropanol can assist hydride shifts within the structure of fructose, similar to the mechanism identified in section .…”
Section: Results and Discussionmentioning
confidence: 97%